Early Identification of Traumatic Durotomy Associated with Atlantooccipital Dislocation May Prevent Retropharyngeal Pseudomeningocele Development - Robert S. Qiu; Mina G. Safain; Max Shutran; Alejandra M. Hernandez; Steven W. Hwang; Ron I. Riesenburger (Case Reports in Surgery)
Atlantooccipital dislocation can be complicated by a traumatic durotomy that may lead to the rare development of a retropharyngeal pseudomeningocele. To our knowledge this has been reported only five times previously. We present the case of a 60-year-old man involved in a motor vehicle accident who suffered an atlantooccipital dislocation and C5-C6 three-column injury. A unique MRI image of a defect in the ventral dura posterior to C2 was appreciated. He underwent occiput to T2 internal fixation and arthrodesis. During surgery, CSF egress was seen caudal to the right C2 nerve root. A DuraMatrix onlay patch reinforced with DuraSeal was placed to stop the CSF leak. A lumbar subarachnoid drain was also placed. The patient made a satisfactory recovery with residual mild weakness of his right upper extremity. In this report, we demonstrate that careful MRI review can reveal a ventral durotomy in a traumatic atlantooccipital dislocation and, if discovered, effective treatment including a lumbar subarachnoid drain for CSF diversion may prevent progression to a retropharyngeal pseudomeningocele. The literature on this rare presentation and associated durotomy is provided.